Property Price, Capital Inflows, and Financial System Stability in ASEAN-5 Economies: A Simultaneous Analysis - Sonia Anggun Andini; Telisa Aulia Falianty (Journal of Indonesian Economy and Business, 2022)
Introduction/Main Objectives: This study aims to estimate the impact of capital inflows on property prices and financial system stability (FSS) in ASEAN-5 and the simultaneous relationship between the two dependent variables. During the observation period of this study, there were large capital inflows to ASEAN 5 countries after the 2008-2009 financial crisis; on the other hand property prices showed an increase in that period. Background Problems: This study indicates the simultaneous relationship between two dependent variables. In fact, using only a single equation for variables that have a simultaneous relationship can cause endogeneity problems, so the results obtained become unreliable/ biased. Novelty: The novelty of our research is we fill a gap in the previous studies by examining the relationship of property prices and financial system stability with the simultaneous method so as to solve the endogeneity problem that exists. Research Methods: We use the 2SLS simultaneous panel model to solve endogeneity problems. Finding/ Results: The results show that the massive capital inflows to ASEAN-5 countries caused a significant increase in property prices. Conclusion: This study confirms that property prices and financial system stability have simultaneous relationships. On the one hand, the impact of property prices on the financial system stability is positive and significant. On the other hand, testing the effect of the financial system stability on property prices does not show significant results.